Implementasi Akad Wakalah Bil Ujrah pada Pembayaran Rekening Listrik - Nur Musayadah; Asiah Wati (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2022)
This individual payment actually makes it easier for people to make electricity bill payment transactions without going out of the house, especially for people who do not travel for certain reasons. The author's background in this study is the public unrest where the author examines the payment of electricity bills through individuals with different ujrah. The formulation of the problem that then arises is how to implement electricity bill payments through individuals in Dukuh Panggilan when reviewed with DSN MUI Fatwa No. 113/DSN-MUI/IX/2017 concerning Wakalah Bill Ujrah. The purpose of the study is to identify the payment of electricity bills in terms of the Fatwa of DSN MUI No. 113/DSN-MUI/IX/2017 concerning Wakalah Bill Ujrah. The research method used is a qualitative method that takes the type of field research, data collection techniques are carried out using observations and interviews. Observations were made as non-participant observers. The results of this study are individuals as representatives in paying electricity bills in Dukuh Panggilan have an important role because of the convenience of residents in paying, especially for society. The existence of ujrah/fees that are not the same from person to person or month to month, also there is no transparency of the amount of ujrah which creates uncertainty, resulting in incompatibility with DSN MUI Fatwa No. 113/DSN-MUI/IX/2017 concerning Wakalah Bill Ujrah. So it is necessary to agree on the amount of ujrah by both parties in order to reach an agreement, so that the contract can be carried out properly.